Attitudes and Experiences of TK Insurants Concerning EU-wide Electronic Exchange of Health Data - Katharina Dobrick (2013)
Information and communication technology (ICT) is becoming increasingly important in healthcare as in all other areas of everyday life, but the implementation of new structures also poses problems concerning data safety and interoperability of systems if introduced EUwidely. The implementation of new systems for health data exchange is costly and will only be profitable if they are widely accepted and applied. In order to get an impression of opinions on electronic health data exchange a questionnaire was sent to TK insurants who have experience with EU cross-border treatments. The questionnaire included questions on attitudes concerning data safety, confidentiality, need for more information on ICT in the EU and further questions on experiences with treatments in the EU. Results showed that the majority agrees that ICT is useful, but experiences showed that only 12 % of the respondents would have wanted better data exchange. An unanticipated after-treatment in combination with dissatisfaction with the data exchange only occurred in 3.4 % of the cases, which shows that the assumed utility of EU-wide ICT is fairly low. Further research on the costeffectiveness of EU-wide health ICT is necessary and as only TK insurants have been included so far, it should include patients from other nations and other social groups, as well.